Дослідження системи переміщення електродів дугової сталеплавільної печі з нечітким регулятором - Лозинський, А.О.; Паранчук, Я.С.; Демків, Л.І. (Інститут електродинаміки НАН України, 2014)
Для системи переміщення електрода дугової сталеплавильної печі проаналізовоно вплив нелінійностей на показники її функціонування та синтезовано нечіткий регулятор, який забезпечує швидкий вихід системи на усталений режим при відсутності коливань вихідної координати системи. Для компенсації збурень використано формування керуючого впливу на основі відхилення напруги дуги від заданого значення. Проведено порівняльний аналіз отриманих результатів з традиційними підходами. Для системы перемещения электродов ДСП проанализировано влияние нелинейностей на функционирование системы и синтезирован нечеткий регулятор, который обеспечивает быстрый выход системы на установившийся режим при отсутствии колебаний выходной координаты системы. Для компенсации возмущений предложено использовать закон управления на основе отклонения напряжения дуги от заданного значения. Проведен сравнительный анализ полученных результатов с традиционными подходами. For electrodes movement system of arc furnace impact of nonlinearities on the system is analyzed. Fuzzy controller, which provides a quick pass of the system to steady state at the absence of fluctuations in the output system’s coordinate, is synthesized. To reduce a complexity of the rule base, a natural fuzzy controller is used. To synthesis the fuzzy controller system’s motion trajectory is divided into two zones: large and small deviations of arc length from initial value. Corresponding linguistic variables have membership function of S-type and Z-type respectively. To compensate the perturbation a control law based on arc voltage deviation from the set value is suggested. It is shown that the use of system which is linearized in the single point of space of state for the synthesis of control actions does not allow classical methods of synthesizing the optimal control for the full range of coordinate changes and disturbances of ASC. The approach to system construction which provides disturbances of various sizes rejection with the necessary speed and without overshoot is proposed. At this, intermediate system’s coordinates are within acceptable limits and ACS is physically realized.